UTILIZATION PROBIOTIC LACTIC ACID BACTERIA FISH FROM WASTE FAECES ON LDL LEVEL BLOOD BROILER CHICKENS STRAIN LOHMANN - Astuti Astuti; Siti Umniyati; Anna Rakhmawati; Evy Yulianti (Jurnal Sains Dasar, 2016)
Abstract This study aims to determine the effect of lactic acid bacteria supplement from sewge force feeding fish to the LDL content of broiler chicken blood. The research samples are 40 of 1 day old broiler chicken from PT. Multi Breeder Adiram, which were divided into 4 treatments, were taken randomly and maintined for 42 days. Data were analyzed by analysis of variance using a completely randomized design unidirectional pattern, followed by a test of Duncan's Multiple Range Test (DMRT).Probiotic Lactic Acid Bacteria Isolates treatment (BAL) were used in this study is the bacterium Streptococcus thermopillus in the form of freeze drying from the Laboratory of Nutritional Biochemistry, Faculty of Animal Husbandry, UGM. I as a control treatment (without BAL) Treatment II BAL cell count was 106 CFU / ml., The third treatment is the number of BAL Cells are 107CFU / ml. , IV treatment BAL cell count was 108 CFU /ml. The results showed that there is no significant effect of BAL isolate addition on the LDL level of the broiler chicken blood. Keywords: lactic acid bacteria, LDL, freeze drying